Unusual dye adsorption behavior of kappa-carrageenan coated superparamagnetic nanoparticles - Salgueiro, Ana M.
kappa-Carrageenan coated magnetic iron oxide nanoparticles (NPs) were synthesized and tested as adsorbents for the magnetically assisted removal of methylene blue (MB) from aqueous solutions, a cationic dye commonly present in wastes from the textile industry. The resulting composite NPs were superparamagnetic and contained ca. 12 wt% carrageenan. The MB uptake ability was found to vary with the pH solution and was larger in alkaline conditions. Both pseudo-first-order and pseudo-second-order equations predicted well the kinetics with the maximum adsorption achieved very fast, within 5 min. The MB adsorption has shown an unusual Z-type isotherm which suggests the generation of new adsorbing sites with increasing MB initial concentration. Under the experimental conditions used (23 degrees C, pH 9) the materials presented here displayed MB adsorption capacity (185.3 mg/g) higher than other magnetic sorbents previously reported. Thus x-carrageenan coated magnetic NPs are very promising eco-friendly materials for removing MB from wastewater using magnetic separation. (c) 2013 Elsevier B.V. All rights reserved.